Magnetic Material for Motor Drive Systems Fusion Technology of Electromagnetic Fields - Fujisaki, Keisuke (Engineering Materials,, 2019)
This book focuses on how to use magnetic material usefully for electrical motor drive system, especially electrical vehicles and power electronics. The contents have been selected in such a way that engineers in other fields might find some of the ideas difficult to grasp, but they can easily acquire a general or basic understanding of related concepts if they acquire even a rudimentary understanding of the selected contents. The cutting-edge technologies of magnetism are also explained. From the fundamental theory of magnetism to material, equipment, and applications, readers can understand the underlying concepts. Therefore, a new electric vehicle from the point of view of magnetic materials or a new magnetic material from the point of a view of electric vehicles can be envisioned: that is, magnetic material for motor drive systems based on fusion technology of an electromagnetic field. Magnetic material alone does not make up an electric vehicle, of course. Other components such as mechanical structure material, semiconductors, fuel cells, and electrically conductive material are important, and they are difficult to achieve. However, magnetic material involves one of the most important key technologies, and there are high expectations for its use in the future. It will be the future standard for motor-drive system researchers and of magnetic material researchers as well. This book is a first step in that direction.